(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
The ore knot is placed on crossing through upper mantle-crust NE and crust NW breaks, where the magmatic formations are intensively shown in different depths of formation, field and zone of hydrothermal-metasomatic transformed rocks, endogenous ore accumulation. It is distinguished by geological-structural, aerospacedistanced datа, local geophysical and geochemical anomalies.